Cardiac magnetic resonance imaging of non-ischaemic cardiomyopathy. Issue 1035 (1st July 2011) - Deshpande, Aparna; Pakkal, Mini; Agrawal, Bobby; Raj, Vimal
Abstract : Cardiomyopathy is defined as a heterogeneous group of diseases of the myocardium associated with mechanical and/or electrical dysfunction due to a variety of causes that are frequently genetic. These are either confined to the heart or are part of generalised systemic disorders, often leading to cardiovascular death or progressive heart failure related disability. Determination of exact aetiology of cardiomyopathy can be difficult but remains important for both treatment and prognosis. Cardiovascular magnetic resonance imaging allows comprehensive assessment of patients suspected to have cardiomyopathy and is therefore being increasingly used in diagnosis and follow-up of these patients. This review presents the main features of common cardiomyopathies on cardiovascular magnetic resonance imaging and highlights its role in providing additional information over and above the traditional diagnostic techniques.